(untitled) (The International Journal of Educational Sciences and Arts, 2026)
The current research aimed to identify the nature of the relationship and correlation between competitive anxiety, self-confidence, and the accuracy of performing (passing and dribbling) football skills among female students at Ashur University. The researcher used a descriptive correlational approach, as it was suitable for the nature of the study, on a sample of (30) female students from Ashur University, selected randomly. The researcher used the CSAI-2 scale to measure psychological variables and standardized skill tests to measure performance. The results showed a statistically significant inverse correlation between anxiety and skill performance, while self-confidence showed a strong positive correlation with performance accuracy (P ≤ 0.05). The research concludes that emotional stability and enhanced self-confidence are fundamental pillars for developing motor learning and consolidating skills among beginner students.